Classroom management and preschool children’s social behaviors - Ayşe yakupoğulları; İsa Kaya (Institute of Advanced Engineering and Science, 2026)
Classroom management is widely recognized as a core component of early childhood education. While previous studies have largely focused on its relationship with academic outcomes, its role in explaining children’s social behaviors in early childhood classrooms has received comparatively less attention. This study examines how preschool teachers’ classroom management skills are associated with children’s positive and negative social behaviors. The study was designed within a correlational framework and included 25 preschool teachers and 339 children enrolled in their classes. Data were collected using the preschool teachers’ classroom management skills scale and the social behavior scale for preschool children and analyzed using Pearson correlations and multiple regression analyses. The results revealed a moderate and statistically significant positive relationship between teachers’ overall classroom management skills and children’s overall social behavior levels. Among the dimensions of classroom management, planning–program implementation and physical arrangement emerged as significant predictors of children’s emotional competence. These findings indicate that classroom management functions not only as an organizational practice but also as a contextual factor supporting children’s social and emotional development. Strengthening preschool teachers’ classroom management skills through practice-oriented professional development initiatives may contribute to the promotion of positive social behaviors in early childhood settings.